ANALISIS KESALAHAN DALAM MENYELESAIKAN SOAL-SOALSTATISTIKA PADA PEMBELAJARAN PASCA COVID-19 - Kartika, Era Dewi; Hanifatulianti, Fharanida Ilmalana (Universitas Insan Budi Utomo, 2022)
The research in this article was conducted with the aim of analyzing students' mistake in solving problems on statistical material. The subject matter of statistical material is related to the presentation of data in the form of diagrams and tables, average in problem solving, median and mode. This research belongs to the typeof descriptive research using qualitative research methods. The test instrument is theinstrument used in this study which consists of 5 multiple choice questions, eachof which contains indicators of student competency achievement. The analysis of thelevel of student difficulty was carried out after the data was collected based ontheresults of the written test that had been done. Based on the data collected will bedisclosed, analyzed, and described in words about the difficulties of students instatistical material. Based on the results of the study, it was concluded that student errors in working on problems on statistical material, namely students makemistakes on indicators determining the data value of the two average values, withanerror percentage of 80%. besides that, students also had errors in the indicators of determining the pie chart that matched the data, with a percentage error valueof 60%.